Satya, prem ani katuta : Khushwant Singh yanche atmacharitra - Sigh Khushwant Singh ; Murgudkar Chandrashekhar (Tr.) (Chinar Publishers, Pune, 2003)
Marathi
UGC X PLAN (2002-2004)
MARATHI
Keywords: Satya, prem ani katuta : Khushwant Singh yanche atmacharitra; Marathi; Marathi